ANALISIS MANAJEMEN RISIKO PADA SISTEM INFORMASIKIMIA FARMA EMPLOYEE SELF TECHNOLOGY(STUDI KASUS : PT KIMIA FARMA TBK) - Alya Nur Ramadhani (2022)
The role of technology in human activities at this time is indeed very big. Almost all organizations have made information technology a necessity and important for organizations in carrying out various business processes. In dealing with this situation, the company formed an IT (Information and Technology) Division which focuses on helping the ease of running the company's activities, by developing and creating applications that can support the activities of its employees. Applications that have been created by the IT Division can be accessed through a portal called KIFEST (Kimia Farma Employee Self Technology). KIFEST is an integrated service employee information system application for Kimia Farma's internal employees that displays all applications in one main application page. With the ease of accessing these applications, of course, there are threats and risks to this integrated service information system for internal employees. This risk will result in losses for a company, so it is important to carry out existing risk management by identifying and measuring them. KIFEST was released in 2017. From the data collection process using interview techniques, information was obtained regarding possible risks that exist in the company, namely there is a risk of data loss, hacking, invalid data, server down, human error, cybercrime, and failed updates which are then analyzed further in this research. The purpose of this study was to analyze the risk management of Kimia Farma Employee Self Technology Information System. To carry out risk management analysis the author uses the ISO 31000 method. From this research, the results of risk analysis are obtained, namely there are 27 possible risks with 5 levels of risk consisting of 1 possible risk with a high level of risk, 1 possible risk with a moderate to high level of risk, 6 possible risk with a moderate level, 8 possible risks with a low to moderate risk level, and 11 possible risks with a low risk level. The risk levels are sorted from highest to lowest, the list of risk management analysis results can be used as a benchmark and basis for making decisions as well as advice on risk treatment of the possible risks that exist.